Bypassing Islamism and Feminism: Women’s Resistance and Rebellion in Post-revolutionary Iran - Fatemeh Sadeghi (Revue des Mondes Musulmans et de la Méditerranée)
This paper explores the reason behind the crisis of representation in post-revolutionary competing Iranian gender discourses. These competing discourses include Islamic fundamentalism, religious revisionism, and secular feminism. The crisis of representation is related to at least three main presuppositions and attendant action programs: first, discrimination against women and possible accommodations should be examined in the context of religious and legal institutions. This approach resulted in the depoliticization of women’s issues, even though most Iranian women have persistently proclaimed equality and citizenship through political participation. This was the case for the 1979 Islamic Revolution, the reform movement and most recently, the Green Movement following the 2009 presidential election. The second presupposition is that individual identity is a fundamental condition for socio-political activism. The third presupposition is that discrimination against women in post-revolutionary Iran is essentially a legalist strategy and has resulted in campaigns that failed to address women’s daily challenges. On the contrary, women’s political participation in post-revolutionary Iran shows that gender issues are always political issues and need to be understood politically and politicized. Such a notion challenges attitudes which relegate gender discrimination and social solutions to the purview of religion or secularism.